Unravelling the mechanisms by which chronic hepatitis B infection is associated with an increased risk of gestational diabetes - Subashree Paramasivam; Sushena Krishnaswamy; Michelle L Giles (Frontiers Media S.A., 2023)
An independent association between chronic hepatitis B virus (HBV) and the development of gestational diabetes (GDM) has been reported in the literature. Ethnic background and regional influences have been demonstrated to play a role in the reporting of incidence rates of GDM among women with chronic HBV. The mechanisms behind this association are poorly understood, but evidence suggests an inflammatory basis. Viral factors such as chronic HBV replication, quantifiable by HBV viral load, have been proposed to contribute to the increasing risk of insulin resistance in pregnancy. More research is needed to better characterise the association and determine if any interventions early in pregnancy for women infected with chronic HBV would mitigate the development of GDM.